Temperature-Dependent Charge Transport through Individually Contacted DNA Origami-Based Au Nanowires - Teschome, Bezu (Langmuir : the ACS journal of surfaces and colloids, 2016)
DNA origami nanostructures have been used extensively as scaffolds for numerous applications such as for organizing both organic and inorganic nanomaterials, studying single molecule reactions, and fabricating photonic devices. Yet, little has been done toward the integration of DNA origami nanostructures into nanoelectronic devices. Among other challenges, the technical difficulties in producing well-defined electrical contacts between macroscopic electrodes and individual DNA origami-based nanodevices represent a serious bottleneck that hinders the thorough characterization of such devices. Therefore, in this work, we have developed a method to electrically contact individual DNA origami-based metallic nanowires using electron beam lithography. We then characterize the charge transport of such nanowires in the temperature range from room temperature down to 4.2 K. The room temperature charge transport measurements exhibit ohmic behavior, whereas at lower temperatures, multiple charge transport mechanisms such as tunneling and thermally assisted transport start to dominate. Our results confirm that charge transport along metallized DNA origami nanostructures may deviate from pure metallic behavior due to several factors including partial metallization, seed inhomogeneities, impurities, and weak electronic coupling among AuNPs. Besides, this study further elucidates the importance of variable temperature measurements for determining the dominant charge transport mechanisms for conductive nanostructures made by self-assembly approaches